Correction of metal artefacts around orthodontic mini-implants – a micro-CT study in the rat tail model - Robert Kerberger; Giulia Brunello; Nicole Rauch; Dieter Drescher; Bert van Rietbergen; Kathrin Becker (Scientific Reports)
Abstract Micro-CT enables volumetric analysis of peri-implant tissue, but grey value alterations due to metal artefacts can impair analyses. This study aimed to assess to which extent peri-implant grey values are affected by metal artefacts at increasing distance to the implant, and whether mathematical correction is possible. In nine rats, two Ti6Al4V orthodontic mini-implants (OMIs), 0.8 mm in diameter and 3.0 mm in length, were placed in a single tail vertebra. Micro-CT scans were performed before (T0) and after (T1) careful removal of the OMIs. Consecutive micro-CT scans were registered and differences in local grey values were computed at increasing distance to the implant (10.4 μm to 405.6 μm). Correction coefficient (CC) computation was performed using a smoothing spline fit, with the distance to the implant and the grey value difference as independent and dependent variable, respectively. To validate the effectiveness of the CC, the amount of calcified bone volume per total volume (BV/TV) was assessed within a standardized volume of interest (VOI) reaching up to 1 mm around the OMIs before and after the application of CC, and the T1-T0 differences between corrected and uncorrected scans were compared using the Wilcoxon signed-rank test. The grey value difference between uncorrected T0 and T1 scans was low in proximity to the implant (32.7%±6.11%) and improved at a distance of at least 100 μm (93.4%±4.46%). CC computation revealed a satisfactory fit (R2 = 0.989, RMSE = 0.031) and the difference in grey values was significantly lower after correction (p < 0.001). Most VOIs showed significant improvement, though overcorrection was observed in a few cases. Within the limitations of the study, metal artefacts decreased with increasing distance to the OMIs, and significant improvement was possible using the CC.